Analysis of oxylipins to differentiate between organic and conventional UHT milks. (1st May 2021) - Samarra, Iris; Masdevall, Clara; Foguet-Romero, Elisabet; Guirro, Maria; Riu, Marc; Herrero, Pol; Canela, Núria; Delpino-Rius, Antoni
Highlights: Fatty acid, TAG and oxylipin profiles measured in organic and conventional UHT milks. Fatty acid, TAG and oxylipin profiles are affected by organic vs. conventional production. Individual TAG profile could differentiate between organic and conventional production. Fourteen oxylipins derived from ARA, ALA, EPA and LA are biomarkers of organic milk. Oxylipin analysis can be a robust organic milk authentication method. Abstract: Nowadays, there is a strong interest in analytical approaches for assessing organic farming practices. Here, we propose that oxylipins, a group of oxidised metabolites derived from various polyunsaturated fatty acids, could be promising biomarkers for organic milk assessment because their biosynthesis is modulated by both precursor fatty acid availability and physiological or pathological status. Thus, we determined 31 fatty acids, 53 triacylglycerols and 37 oxylipins in one hundred commercial UHT milks by chromatographic methods coupled to mass spectrometry. Of these, 52 milks were conventional (34 whole milk, 11 semi-skimmed milk and 7 skimmed milk) and 48 were organic (31 whole milk, 11 semi-skimmed milk and 6 skimmed milk). Several oxylipins (8-HEPE, 5-HEPE, 11-HEPE, 9-HEPE, 18-HEPE, 9-HOTrE, 13-HOTrE, 12, 13-DiHODE and 15, 16-DiHODE) could distinguish between organic and conventional milks. Within these oxylipins, arachidonic and linoleic acid derived do not correlate with their fatty acid precursors; therefore these oxylipins could be promising as not only diet-dependent biomarkers for organic milk assessment.